Batkoa apiculata (Thaxter) Humber affecting Anopheles (Diptera: Culicidae) in the municipality of Una, Southern Bahia, Brazil. - Méndez Sánchez, Saúl Edgardo; Humber, Richard; Freitas, Adriano; Pinheiro, Adélia Ma.C. M. (ENTOMOTROPICA, 2011)
Surveys for fungal pathogens affecting adult mosquitoes from the genus Anopheles were conducted in flooded and swamp-like natural breeding sites near residences in the center and suburbs of the city of Una as well as the nearbyvillage of Outeiro in southern Bahia. Surveys of 54 mosquito breeding sites over a period of 24 months yielded 150 sample collections with a total of 194 Anopheles cadavers infected by the pathogenic fungus Batkoa apiculata(Entomophthorales: Entomophthoraceae). Apart from their basic scientific value, these results also offer some hope about the possibilities to use fungus-based biocontrol against Anopheles species that vector malaria in Brazil.